(untitled) (Geographical Journal of Nepal, 2018)
Open space is essential part of city life because it provides an opportunity for recreation, playing, religious activities, political activities, cultural activities and so on. This paper discusses the types of open space and its distribution in Pokhara Lekhanath Metropolitan City (PLMC). An inventory of open spaces was prepared based on the available analog maps with intensive field verification. There are eight major and 32 subtypes of open spaces with a total number of 246 within the PLMC. The main types of open spaces are park, playground, religious site, water surface, cave, aesthetic view point, river strip and messy places. Those open spaces vary in form, size, ownership and functions. The distribution of open spaces is not uniform among the 33 Wards in the Pokhara Lekhanath Metropolitan City. The number of open space varies from only one to twenty-one and total area of open space varies from only 51 ha to 4786 ha among those Wards. Per capita area of open space ranges from 0.16 to 659 m² among those wards. In many wards, per capita area of open space is less than 9 m² which is recommended by FAO. Such a poor situation is created mainly due to the lack of public land use planning, encroachment in open space for development of infrastructure such as public buildings, and lack of knowledge about the importance of open spaces among decision makers and local people and weak capacity of local people to protect and conserve open space from encroachment. The Geographical Journal of Nepal Vol. 11: 25-44, 2018